2020
DOI: 10.1002/ijgo.13134
|View full text |Cite
|
Sign up to set email alerts
|

Using mHealth in postpartum women with pre‐eclampsia: Lessons learned from a qualitative study

Abstract: Objective: To explore perceptions and attitudes of postpartum women with preeclampsia towards remote monitoring (mHealth) and communication with the call center. Methods:A non-randomized cohort study was conducted in postpartum hypertensive women, recruited from a tertiary hospital between October 2015 and February 2016. Participants were categorized into users (using mHealth) and non-users (not using mHealth) to monitor vital signs at home over a 2-week period after discharge.Non-users were informed about fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Using apps to support pregnant women enhances the traditional pregnancy care model by providing additional educational information and empowering women to look after their own health [ 21 , 23 - 26 ]. Sensors and monitoring technologies that automatically track specific health indicators have been integrated into mHealth solutions to support pregnant women’s self-care behaviors [ 22 , 27 - 29 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using apps to support pregnant women enhances the traditional pregnancy care model by providing additional educational information and empowering women to look after their own health [ 21 , 23 - 26 ]. Sensors and monitoring technologies that automatically track specific health indicators have been integrated into mHealth solutions to support pregnant women’s self-care behaviors [ 22 , 27 - 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Even with emerging evidence on the potential benefits, barriers to the implementation of mHealth technologies in pregnancy care persist [ 19 , 24 , 27 , 28 , 38 ]. Various factors can impact an individual’s feeling toward sharing and tracking health data, including stress associated with mHealth monitoring, the availability of reliable educational information, and ineffective communication with clinicians [ 22 , 25 , 27 , 30 ]. Further research is needed to understand pregnant women’s motivation to use technologies to better support their engagement, data collection compliance, and daily use [ 27 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Patients reported a reduction in the frequency of routine follow-up or urgent visits. This was particularly relevant for those who lived in remote areas, had mobility issues, or lacked resources and time—“Having (blood pressure device) at home would be a lot less stressful than having to go out and have it monitored.” 39 Others reported discomfort in sitting in the waiting room—“It was really uncomfortable to sit for half an hour, so by the time I got upstairs, my blood pressure was high.” 19 …”
Section: Resultsmentioning
confidence: 99%
“…Some believed that daily monitoring of blood pressure was redundant because blood pressure was already being managed by their GPs. Patients felt that continuous monitoring could make people “hypochondriac.” 19 Some thought that self-monitoring of blood pressure added more responsibilities in their daily lives and “it would be overwhelming.” 39 Some felt “bored” 25 with continuous monitoring. Some remarked that if patients “are adherent to medications, there was no need to check blood pressure.” 15 …”
Section: Resultsmentioning
confidence: 99%
“…Further perceived advantages and disadvantages associated with the RPM BP device were explored in a semi-structured interview. Previous research on RPM for hypertension has focused on postpartum women (Payakachat et al, 2020 ; Hoppe et al, 2019 ) or used Bluetooth devices that require a smartphone and app (Ganapathy et al, 2016 ; Marko et al, 2016 ). In a small pilot study that aimed to assess the feasibility of using Bluetooth RPM BP devices for prenatal care, it was found that patients demonstrated high satisfaction with the device (Marko et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%